2013
DOI: 10.1186/1471-2148-13-31
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia association with the tsetse fly, Glossina fuscipes fuscipes, reveals high levels of genetic diversity and complex evolutionary dynamics

Abstract: BackgroundWolbachia pipientis, a diverse group of α-proteobacteria, can alter arthropod host reproduction and confer a reproductive advantage to Wolbachia-infected females (cytoplasmic incompatibility (CI)). This advantage can alter host population genetics because Wolbachia-infected females produce more offspring with their own mitochondrial DNA (mtDNA) haplotypes than uninfected females. Thus, these host haplotypes become common or fixed (selective sweep). Although simulations suggest that for a CI-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 51 publications
(81 reference statements)
4
18
0
Order By: Relevance
“…It is also possible that Wolbachia -induced mating incompatibility is driving the differentiation between the population structure inferred from mitochondrial and nuclear DNA. Wolbachia mediated effects on host fitness and host population genetic can drive patterns of mtDNA variation regardless of the nuclear DNA background [36, 61, 62]. A finer scale analysis of Wolbachia infection prevalence and strain types present in flies in the contact zone is necessary to further clarify the role of Wolbachia mediated reproductive effects.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that Wolbachia -induced mating incompatibility is driving the differentiation between the population structure inferred from mitochondrial and nuclear DNA. Wolbachia mediated effects on host fitness and host population genetic can drive patterns of mtDNA variation regardless of the nuclear DNA background [36, 61, 62]. A finer scale analysis of Wolbachia infection prevalence and strain types present in flies in the contact zone is necessary to further clarify the role of Wolbachia mediated reproductive effects.…”
Section: Discussionmentioning
confidence: 99%
“…In field G. m. morsitans , Wolbachia infection prevalence ranges from 10 to 100% depending on their resident habitats (Doudoumis et al, 2012). Some G. fuscipes individuals also harbor infections with multiple Wolbachia strains (Symula et al, 2013). For example, Wolbachia strains detected in Ugandan G. fuscipes belong to two different lineages.…”
Section: Tsetse-microbe Associations In Natural Populationsmentioning
confidence: 99%
“…Previous surveys using standard PCR assays could not detect Wolbachia infections in Gff in Uganda or Kenya [78,79]. When more stringent PCR assay conditions and qPCR analysis were used, low-density Wolbachia infections were detected in different Gff populations [80]. The infection prevalence in different host genetic populations ranged from zero to complete fixation, with the greatest prevalence observed in the southern genotypes, followed by northern and western genotypes (55%, 42%, and 26%, respectively) [80].…”
Section: Tsetse Microbiota As Influential Factors Of Vector Competencementioning
confidence: 99%
“…When more stringent PCR assay conditions and qPCR analysis were used, low-density Wolbachia infections were detected in different Gff populations [80]. The infection prevalence in different host genetic populations ranged from zero to complete fixation, with the greatest prevalence observed in the southern genotypes, followed by northern and western genotypes (55%, 42%, and 26%, respectively) [80]. To understand Wolbachia evolutionary dynamics and their relationship with host mtDNA, populations of known genetic background were screened for Wolbachia infection status, which showed that Wolbachia infections in Gff are not limited to a single host mtDNA haplotype [80].…”
Section: Tsetse Microbiota As Influential Factors Of Vector Competencementioning
confidence: 99%